First isolation, identification and genetic characterization of Brucella abortus biovar 3 from dairy cattle in Bangladesh. Issue 4 (26th August 2019) - Islam, Md. Sadequl; Garofolo, Giuliano; Sacchini, Lorena; Dainty, Amanda C.; Khatun, Mst. Minara; Saha, Sukumar; Islam, Md. Ariful
Abstract: Background: Brucellosis is a zoonotic disease caused by bacteria Brucella spp. belonging to the genus Brucella . It is endemic in domesticated animals in Bangladesh. Isolation, identification and genetic characterization of Brucella spp. in dairy cattle are essential to undertake appropriate control and preventive measures. The study was conducted to isolate and characterize the Brucella spp. circulating in dairy cattle. Methods: Uterine discharge ( n = 45), milk ( n = 115), vaginal swab ( n = 71), placenta ( n = 7) and aborted fetus ( n = 2) were collected. Brucella selective agar plates were inoculated with samples and incubated at 37 ◦ C for 14 days under 5% CO2 for isolation of Brucella spp. Brucella suspected colonies were recovered from samples were confirmed by genus and species specific PCR assays. Genetic characterization was performed by Multi Locus Variable number tandem‐repeat Analysis‐16 (MLVA‐16). Results: The isolates of Brucella recovered from samples were confirmed as B. abortus by AMOS‐ERY PCR assay. The classical biotyping method confirmed all 10 B. abortus isolates belonged to the biovar 3. The MLVA‐16 assay indicated all B. abortus isolates identical and the same genotype 40, based on panel 1 MLVA‐8. Conclusion: Dendrogram analysis revealed all B. abortus isolates of the study were identical to three isolates from Brazil, one isolate of France and closely related to Chinese isolates. This is the first report of isolation and genetic characterization of B. abortus from the dairy cattle in Bangladesh. Abstract : This study isolates and identifies 10 Brucella abortus biovar 3 from the dairy cattle experiencing abortion. Multi Locus Variable number tandem‐repeat Analysis‐16 (MLVA‐16) revealed all B. abortus isolates of the study were identical to three isolates from Brazil, one isolate of France and closely related to Chinese isolates. This is the first report of isolation and genetic characterization of B. abortus biovar 3 from the dairy cattle in Bangladesh.